Risk (Concepts in the Social Sciences) - Roy Boyne (Great Britain Open University Press, 2003)
The term risk occurs throughout contemporary social analysis and political commentary. It is now virtually a legal requirement that large organizations throughout the world establish formal risk assessment and risk management procedures. Increasingly dense communication and media networks alert huge numbers of people and organizations to a widening range of threats and possibilities. A basic understanding of the risks themselves may require specific technical knowledge of basic chemistry, or the psychology of motivation, or of contrasting interpretations of injustices deep within the past. However, at the same time as attending to specific risks, there are general questions such as those above which invite reflection.
Keywords: Risk; Risk Management; Textbooks; Global Business Dynamics (BIN2043-N)